Changing gear: Experiences of how existing qualitative research can adapt to an unfolding health emergency - Jones, Theresa; Enria, Luisa; Lees, Shelley; Marchant, Mark; Tulloch, Olivia (Frontiers in Sociology, 2022)
Long-term research projects are not always able to adapt to a new crisis and incorporate some of the characteristics and approaches of rapid research, to produce useful data quickly. Project AViD was a programme of research that ran between 2018-2022 to examine factors that shape vaccine confidence. The project initially focused on five country case studies looking at vaccines for Ebola, Measles, Rift Valley Fever and Zika. The COVID-19 pandemic emerged during this time and provided an opportunity to contribute to the pandemic’s ‘million-dollar question’ - how to deploy COVID-19 vaccines. Drawing on our experience as researchers, and specifically from AViD, we propose seven factors that can influence how longer-term qualitative research projects can adapt and contribute to the response to an unfolding health emergency. These include: 1) the phase of research in which the emergency hits; 2) the relative significance of the emergency in the research setting; 3) the specific methods and research team capacities; 4) existing operational links; 5) supportive ecosystems; 6) flexibility in research contracting and funding; and 7) the research team attitude and approach. We close with two considerations for longer-term research projects that find themselves having to ‘change gear’ amid a public health emergency - the need to re-assess risks and benefits and the need to protect equitable partnerships.